Engagement e ambiente de trabalho: um estudo com os profissionais da enfermagem - Garbin, Keiti (2018)
In the field of worker health, nursing professionals present a high degree of vulnerability to stressors. This category of workers is more susceptible to illness, through physical and emotional exhaustion, depending on the characteristics of the work process. Your illness affects your individual and family well-being and performance in the work environment, including interpersonal relationships. Engagement is characterized as a state of energizing, dedication, and engaging individuals while they are working. His studies emerged from the perspective of positive psychology as one of the possible outcomes for workers with Burnout Syndrome as an inverse effect to emotional exhaustion and depersonalization. The dissertation aims to identify the characteristics of the engagement of workers of nursing professionals in the health services. This is a cross-sectional, descriptive complexity study with a quantitative approach that results from simple random probabilistic sampling. Nine hu ndred nursing professionals enrolled in the Regional Nursing Council in the state of Rio Grande do Sul participated. The research instrument includes sociodemographic questions and the brief Engagement questionnaire from Utrecht. The results evidenced an average level of engagement among nursing professionals, both nurses and technicians or nursing auxiliaries, highlighting the importance of dedication as a predictor atribute